Practices of sympoiesis versus the seducing allure of contemporary perplexities - Lacerda-Nobre, Â.; Karamanli, A.; Puskas, N.; Gameiro, A.; Duarte, R.; Jacquinet, M. (Ata livro de conferência - Social Solidarity Economy & the Commons Conference (4th edition, Lisbon, 13-15 November 2024), 2025)
International Relations scholarly production takes into account the micro and the macro scale, i.e., time and space contexts that capture both political and economic regimes, as well as livelihoods and practical life-supporting and life-enhancing functions and social roles. When addressing human faculties, such as memory, will or imagination, and understanding the ultimatum nature of current challenges, the pluri-crises, social and ecological and beyond, it is possible to argue that it is imagination that takes the lead. In other words, outstanding vanguard pioneer action is being taken by bottom-up governance, grass-roots initiatives, transnational networking and community-led action. This action is fuelled by imagination, that is, by the possibility of envisioning an alternative possible future. It is this imagination exercise that uses memory as a powerful resource and will as a detonator, a catalyser and energiser of free action and of free thought, individually and collectively. Focusing on real life examples and tackling the macro level rationale it is possible to suggest new perspectives, to explore a novel hindsight and to propose new prospective analysis and insights. History is history but the future is perfect.